Feed restriction and insulin-like growth factor-I (IGF-I) affect the oocyte maturation in matrinxã Brycon amazonicus - Montrezor, Luís Henrique; Urbinati, Elisabeth Criscuolo [UNESP] (Cambridge University Press (CUP), 2017)
Summary The feeding and nutrition of breeders are crucial aspects in the reproductive process. During the maturation period, metabolic changes occur aiming at mobilizing energy for growth and follicular development. The involvement of IGF-1 in metabolic and reproductive events is important. The aim of this work was to evaluate if alternate feed restriction and re-feeding have permissive effects on in vitro actions of IGF-1 on oocytes development of matrinxã. In vivo experiments were performed during vitellogenesis period. Females (n = 60) were fed with a commercial feed (2% of biomass) and they were divided into two treatments: fish receiving food daily (control-fed), and fish submitted to cycles of 3 days of feed restriction and 2 days of re-feeding (no-fed group). For the in vitro experiments, oocytes (n = 20) were obtained from the ovaries removed at the end of the in vivo experiment and were divided into four groups: fed-IGF-1; fed +IGF-1; no-fed-IGF-1 and no-fed +IGF-1. Fish under restriction had lower body weights, decreased plasma glucose, increased triglycerides levels, and their final maturation and mature oocyte were reduced and the atresic ones were in higher number. Moreover, IGF-1, in vitro, increased the percentage of mature oocytes in fed females and decreased the atresic ones. In no-fed females, IGF-1 increased the final maturation and mature oocytes and reduced the atresic ones. This study demonstrates the importance of the feeding management of female breeders of matrinxã during the vitellogenesis period.
Keywords: Fish; Food restriction; IGF-1; Matrinxã; Oocyte development